Evaluation of Clinical Spectrum of Kala Pathar Poisoning at Jinnah Hospital Lahore - Ali Rehan, Sidra Sonia Chaudhry, Imran Ahmed Moinuddin, Naveed Nayyer, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To study the frequency of different clinical presentations of kala pathar poisoning at Jinnah Hospital Lahore. Study design: Cross sectional study Place and Duration: Department of Medicine, Jinnah Hospital, Lahore from April 2021 to October 2021. Methodology: A total of 90 patients with h/o kala pathar poisoning of both sex and of age 20-50 year were included. Case sheet of patients were prepared for age & sex and clinical presentation i.e. pain in throat, dysphagia, dysphonia, cervico-facial edema, difficulty in opening mouth, dark urine, acute renal failure, sinus tachycardia and sinus bradycardia. Results: Mean age was 33.69 ± 7.91 years. Out of 90 patients, 54 (60.0%) were males and 36 (40.0%) were females with male to female ratio of 1.5:1. Mean duration of kala pathar intake was 7.33 ± 5.86 hours. The main presentation of kala pathar poisoning was pain in throat (98.89%), dysphagia (100%), dysphonia (100%), cervico-facial edema (97.78%), difficulty in opening mouth (98.89%), dark urine (86.67%), acute renal failure (44.44%), sinus tachycardia (88.89%) and sinus bradycardia (21.11%). Conclusion: This study concluded that pain in throat, dysphagia and dysphonia are the common clinical presentations of kala pathar poisoing followed by cervico-facial edema, difficulty in opening mouth, dark urine, acute renal failure, sinus tachycardia and sinus bradychardia. Keywords: Kala pathar poisoning, dysphagia, dysphonia, angioedema, sinus tachycardia.